Cassava breeding and varietal dissemination in Indonesia during 1975-2000: Major achievements during the past 25 years - Hartojo, Koes; Poespodarsono, Soemarjo; Puspitorini, Palupi (International Center for Tropical Agriculture, 2001)
High-yielding varieties, adapted to local conditions and satisfying local preferences, is one of the most important components of improved technologies. Since cassava is propagated vegetatively using farmers’ own planting material, the use of high-yielding varieties will give substantial economic gains without much additional costs. However, the suitability of certain highyielding varieties could be limited and farmers will continuously require higher yields in order to remain competitive. Thus, breeding and varietal improvement will continue to be necessary. Progress in cassava breeding in Indonesia has been relatively slow, since it depends to some extent on the conscientiousness of the scientists as well as on the priorities of the government. Because of a very limited number of people involved in cassava breeding and recent changes in institutional responsibilities, only six cassava varieties have been officially released since 1978. One of these no longer exists, while some other released varieties were the result of natural hybridization. Two of the six varieties officially released were selected from hybrid seed introduced from CIAT/Colombia. Possibly, two new varieties introduced from the Thai-CIAT program will be released in 2000. In 1995, the national mandate for cassava research was assigned to RILET. The institute’s cassava breeding program was established according to CIAT’s conventional methodology, which consists of hybridization, single plant selection, single row selection, preliminary yield trial, advanced yield trials, multilocational trials and proposal for varietal release. Collaboration with other institutes, universities and private companies were enhanced to try to achieve the release of one new variety each year. Varietal multiplication and dissemination by the government are still very limited. However, since 1999 there has been an aggressive multiplication program as a means to support varietal dissemination. When this program is correctly implemented there will be an exponential increase in the area planted to high-yielding varieties. Since 1995 the government of Indonesia has established provincial-level institutes, called Assessment Institute for Agricultural Technology, with the responsibility to adapt new technologies to local conditions and enhance their dissemination and adoption. Collaboration with international as well as other national research centers dealing with cassava will strengthen the research capability and further enrich genetic variability.